THE IMPORTANCE OF WORKING RELATIONS-THE CASE OF VIRGIN - Dr. Ioanna Dimitrakaki (The American Journal of Management and Economics Innovations, 2023)
The promotion and protection of employee mental health at work is an extremely important factor for the scientific management of modern organizations. The advancement of positive mental health can lead to an improved workplace atmosphere and has been linked to positive work-related outcomes, at an employee-level. Especially during period of sudden change and forced reorganizations, as in the case of the latest COVID-19 pandemic, the issue of ensuring positive mental health in the workplace is becoming increasingly important. Until the pandemic broke out, remote work was mainly carried out by highly skilled and highly autonomous workers. Since the outbreak of the pandemic, working from home has been adopted by millions of workers in the EU and around the world. These changes may highlight the importance of understanding the concept of employment relations. The concept may have always been extremely important, but in today's world a deep consideration of its influencing factors is necessary, through the understanding of the ways of strengthening industrial relations in different circumstances (such as in the context of teleworking, hybrid models of physical presence in the office and remote working, etc.). In order for the above to be done, there has to be a deeper comprehension of the ways of strengthening relationships, in different reference contexts and conditions (which requires an increased understanding of the “deep” nature of the concept under study). As a result of the changes brought about by the pandemic, employee stress has increased significantly. This stress was caused by many factors, such as health threats, numerous constraints, isolation, lack of social support, disrupted work-life balance at home, etc.